(untitled) (International journal of artificial intelligence, 2026)
This article examines the possibilities of using digital technologies in physical education classes and their importance in improving the quality of the educational process. Today, modern digital tools such as mobile applications, smart devices, video analysis systems, and online educational platforms are widely used in physical education and sports activities. The article analyzes the effectiveness of these technologies in monitoring students’ physical activity, increasing motivation, organizing individualized training, and improving sports performance. In addition, the advantages and challenges of implementing digital technologies in physical education are highlighted. The study concludes that the integration of digital technologies into physical education lessons enhances educational efficiency, develops students’ interest in sports, and contributes to the formation of a healthy lifestyle.